Clinical and diagnostic value of impairments in electrolyte metabolism in children with acquired myopia (Ukrainian Journal of Ophthalmology, 2025)
Background: Identifying the biochemical features of the body in myopia associated with connective tissue dysplasia is still important in the ophthalmologist’s practice.Purpose: To assess the clinical and diagnostic value of impairments in electrolyte merabolism in children with acquired myopia.Methods: Group 1 included 30 children with mild myopia associated with the syndrome of unspecified connective tissue dysplasia (SUCTD), and Group 2 included 30 children with mild myopia without SUCTD. Group 3 (controls) included 30 pediatric healthy controls without ocular disease. Electrolyte balance was assessed by measuring magnesium, calcium, sodium, potassium and chloride ion concentrations in daily urine.Results: Magnesium and calcium ion concentrations in daily urine in children in Group 1 were significantly (2- and 1.7-fold, respectively) lower compared with children in Group 2, and significantly (2.1- and 1.9-fold, respectively) lower compared with controls (р < 0.05). There was no difference in sodium, potassium or chloride ion concentrations in daily urine among study groups. ROC analysis found that an optimum cutoff magnesium ion concentration of ≤2.3 mmol/day in daily urine was 97% sensitive and 80% specific, with an area under curve value (AUC) of 0.97±0.12 (CI 0.95-0.99) (р < 0.0001). In addition, an optimum cutoff calcium ion concentration of ≤3.42 mmol/day in daily urine was 96% sensitive and 85% specific, with an AUC value of 0.94±0.27 (CI 0.88-0.98) (р < 0.0001). Magnesium ion concentration in daily urine was moderately negatively correlated with dysplasia severity (r= -0.65, р < 0.05), and calcium ion concentration was moderately negatively correlated with dysplasia severity (r= -0.59, р < 0.05).Conclusion: The current study determined the diagnostic values of magnesium and calcium ion concentrations (≤ 2.3 mmol/day and ≤ 3.42 mmol/day, respectively) which can be used as biomarkers for laboratory screening for the presence of SUCTD in clinical practice.
Keywords: myopia; connective tissue dysplasia; diagnostics; electrolytes; urine; children